Nanoindentation analysis of transcrystalline layers in model carbon fiber-reinforced PEEK composite - Sophie Vanpée; Bernard Nysten; Jérémy Chevalier; Thomas Pardoen (Polymer Testing)
Nanoindentation (NI) and atomic force microscopy (AFM) nanoindentation, coupled with polarized light microscopy (PLM), were used to determine the nano-/micromechanical behavior of the amorphous regions and individual crystalline structures, both spherulites and transcrystalline (TC) layers, in PEEK samples containing few carbon fibers. To this aim, thin model samples with a controlled thickness were manufactured to allow both microstructure characterization in transmission mode and indentation tests without substrate effects. Surface roughness of the model samples was carefully minimized to get reliable and low dispersion from indentation experiments. The artefacts and sources of uncertainty of performing indentation experiments on thin polymer films containing some fibers are also discussed. The AFM nanoindentation added value is the possibility of evaluating the mechanical behavior of crystalline structures at the nanoscale, for the determination of mechanical behavior heterogeneities at the intra-spherulitic and intra-transcrystalline scale.